2017
DOI: 10.3892/ijo.2017.3887
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin reverses benzidine-induced epithelial-mesenchymal transition via suppression of ERK5/AP-1 in SV-40 immortalized human urothelial cells

Abstract: Overexposure to benzidine has been manifested as an important cause of bladder cancer. However, the molecular mechanism of benzidine-induced malignancy is still insufficiently interpreted. Epithelial-mesenchymal transition (EMT) is a crucial pathophysiological process in embryonic development as well as initiation and development of epithelium-originated malignant tumors. The role of extracellular regulated protein kinase 5 (ERK5) in benzidine-meditated bladder cancer development has not been explored. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 42 publications
1
19
0
Order By: Relevance
“…Besides, it can modulate numerous signaling pathways, such as transcriptional, signal transduction, and adhesion. 4,12 Evidence suggests that curcumin can regulate different signaling pathways or cytokines to achieve anti-tumor effects, and could be used as an effective adjuvant for cisplatin to regulate the erythroid 2 like 2 (NRF2), nuclear factor, as well as signal transducer and activator of transcription 3 (STAT3) signaling within humans to treat squamous cell carcinoma. 25 According to Woo et al, curcumin inhibited the MAPK signal transduction pathways within astroglioma cells in humans.…”
Section: Dovepressmentioning
confidence: 99%
“…Besides, it can modulate numerous signaling pathways, such as transcriptional, signal transduction, and adhesion. 4,12 Evidence suggests that curcumin can regulate different signaling pathways or cytokines to achieve anti-tumor effects, and could be used as an effective adjuvant for cisplatin to regulate the erythroid 2 like 2 (NRF2), nuclear factor, as well as signal transducer and activator of transcription 3 (STAT3) signaling within humans to treat squamous cell carcinoma. 25 According to Woo et al, curcumin inhibited the MAPK signal transduction pathways within astroglioma cells in humans.…”
Section: Dovepressmentioning
confidence: 99%
“…The ethanol extract of S. chinensis has been reported to suppress streptozotocin-induced EMT in diabetic nephropathy mice by enhancing E-cadherin expression (Zhang et al, 2012). In general, effect of natural products on the metastatic abilities of cancer cells is determined using non-cytotoxic concentration at proper time course (Liu et al, 2017; Kim et al, 2018). In the present study, effects of G.A on EMT, migration, and invasion of CRC cells were determined using lower concentration of 20 uM, which did not significantly decrease the cell viability of CRC cells after G.A treatment for 24 h. The expression level of the epithelial marker E-cadherin concentration-dependently increased, whereas that of the mesenchymal marker N-cadherin and vimentin were decreased by G.A treatment.…”
Section: Discussionmentioning
confidence: 99%
“…And curcumin could inhibit Fra-1/AP-1-mediated gene expression by inhibiting the binding of AP-1 to its cognate motif 92. Liu et al93 also found that curcumin could effectively reduce the low concentration of benzidine-induced EMT in human immortalized urothelial cell (SV-HUC-1 cell line) by inhibiting the ERK5/AP-1 pathway. Therefore, curcumin may inhibit the occurrence of EMT by repressing the expression of EMT-related transcription factors mediated by AP-1.…”
Section: Effects Of Several Common Natural Products On Tumor Emtmentioning
confidence: 99%